2018
DOI: 10.1002/pon.4702
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence is a predictor of survival: A prospective study in women treated for breast cancer

Abstract: This study provides evidence of SOC's predictive value for disease progression and BC-caused and all-cause mortality. Sense of coherence provides a complement when designing individual plans that aims to support patients during their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…We found that the women's SOC tended to be combined with a high sense of meaningfulness and a low sense of compensability or/and manageability. This nding is supported by a cohort study exploring predictors for SOC among women with breast cancer (37). Lindblad et al (37) found a link between a high SOC and coping with life stress for women with breast cancer, as the women used, for example, meaningfulness to accept hormonal treatment even though it had side effects.…”
Section: Relying On Inner Logics and Maintaining Controlmentioning
confidence: 91%
“…We found that the women's SOC tended to be combined with a high sense of meaningfulness and a low sense of compensability or/and manageability. This nding is supported by a cohort study exploring predictors for SOC among women with breast cancer (37). Lindblad et al (37) found a link between a high SOC and coping with life stress for women with breast cancer, as the women used, for example, meaningfulness to accept hormonal treatment even though it had side effects.…”
Section: Relying On Inner Logics and Maintaining Controlmentioning
confidence: 91%
“…Many studies found that higher SOC scores were correlated with greater psychological well-being, higher selfesteem, better general health, more sufficient coping strategies against stress, higher level of quality of life, and better interpersonal relationships. 13,16,[19][20][21] The SOC scale is also strongly and negatively associated with anxiety, anger, burnout, demoralisation, hostility, hopelessness, perceived depression, perceived stressors, and posttraumatic stress disorder. [22][23][24] The literature presents interesting reports confirming the correlation between SOC and emotional adjustment to the disease in women with breast cancer.…”
Section: Manageability Manifests Itself In An Individual's Belief Abomentioning
confidence: 99%
“…Manageability manifests itself in an individual's belief about their capacity to cope with difficult situations, to have an active and effective influence on their own life situation, and to draw conclusions from past experiences. Many studies found that higher SOC scores were correlated with greater psychological well‐being, higher self‐esteem, better general health, more sufficient coping strategies against stress, higher level of quality of life, and better interpersonal relationships . The SOC scale is also strongly and negatively associated with anxiety, anger, burnout, demoralisation, hostility, hopelessness, perceived depression, perceived stressors, and post‐traumatic stress disorder .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…osoby z wyższym poczuciem koherencji cechuje mniejsza śmiertelność z powodu raka piersi, ponadto u chorych z wyższym SOC zauważono zmniejszenie ryzyka progresji choroby. Jednak przy stwierdzeniu współistnienia objawów depresji związek SOC z umieralnością staje się nieistotny [51].…”
Section: Psychosocjalne Aspekty Jakości żYciaunclassified